IoT and Cloud Storage Implementation for Wheat Plant Monitoring at the Tropical Study Center UKSW - Marpaung, Kristian Vieri; Widiasari, Indrastanti R. (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2024)
Information technology in the agricultural sector has been widely discovered, producing large amounts of agricultural products. This research aims to design and build a tool that implements IoT for monitoring agricultural systems using several sensors, converging data communication simultaneously. The real-time between IoT sensors and databases in Cloud Storage and analyzing the performance of agrarian system monitoring systems by implementing IoT and Cloud Storage in the application link which can be accessed on Android or PC. The test results from this research are the performance of the IoT system, which can be accessed using the application Blynk. This IoT works well. MomentBlynkIoT gives commands to the DHT11 sensor and soil moisture sensor to start reading temperature and humidity and then pass it on to the microcontroller and pass it back; BlynkIoT will provide output to the application display in the form of data resulting from sensor performance.